2012
DOI: 10.1038/aja.2011.107
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive changes associated with ADT: a review of the literature

Abstract: The use of androgen deprivation therapy (ADT) has increased since the early 1990s after early detection efforts and greater use of the prostate-specific antigen (PSA) test. Although ADT is associated with favorable clinical outcomes, ADT has been associated with an increased risk for cardiovascular disease, increased serum cholesterol, triglycerides, insulin resistance, body mass index and fat body mass. Here we review findings from 11 clinical studies examining the effects of ADT on cognition as measured by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 56 publications
3
48
0
1
Order By: Relevance
“…Furthermore, it is possible that the additional side effects of ADT, including hot flushes and fatigue, may indirectly influence cognitive function. A recent review of nine clinical studies has also suggested an effect of ADT on spatial memory, but the authors importantly note that only one study was randomised and it did not assess spatial memory (Jamadar et al 2012). Assessment of cognitive and mood parameters in 20 ADT-naïve men at baseline and after 3 and 9 months of treatment, with reassessment after a further 3 months of no treatment, showed a significant decline in spatial reasoning, spatial abilities and working memory during treatment, most evident after 3 months.…”
Section: Mood and Cognitive Functionmentioning
confidence: 99%
“…Furthermore, it is possible that the additional side effects of ADT, including hot flushes and fatigue, may indirectly influence cognitive function. A recent review of nine clinical studies has also suggested an effect of ADT on spatial memory, but the authors importantly note that only one study was randomised and it did not assess spatial memory (Jamadar et al 2012). Assessment of cognitive and mood parameters in 20 ADT-naïve men at baseline and after 3 and 9 months of treatment, with reassessment after a further 3 months of no treatment, showed a significant decline in spatial reasoning, spatial abilities and working memory during treatment, most evident after 3 months.…”
Section: Mood and Cognitive Functionmentioning
confidence: 99%
“…Some men undergo androgen-depriving treatments that indirectly suppress E2-notably advanced prostate cancer patients and male-to-female transsexuals. Cognition in these individuals may be affected due to low circulating steroids [42]. However, whether any E administration after androgen suppression improves cognitive function in males is controversial and warrants further investigation [1,[42][43][44][45].…”
Section: Changes In Ers In the Hc And Pfcmentioning
confidence: 97%
“…Twenty-eight reviews (Ahles & Saykin 2007;Artherholt & Fann 2012;Beauchet 2006;Biegler et al 2009;Chen & Petrylak 2004;Chism & Kunkel 2009;Droz et al 2010;Falci et al 2009;Green et al 2005;Grossmann & Zajac 2011;Gruca et al 2012;Harrington et al 2010;Holzbeierlein 2006;Isbarn et al 2009;Jamadar et al 2012;Janelsins et al 2011;Mitsiades et al 2008;Mohile et al 2009;Mottet et al 2006;Nelson et al 2008;Scherr & Pitts 2003;Sharifi 2005;Trost et al 2013;Tombal 2009;Wefel et al 2004;Wright et al 2006;Ziółkowska et al 2012) described twenty primary studies (Alibhai et al 2010;Almeida et al 2004;Beer et al 2006;Beer et al 2004;Bloomfield & Shilling 2004;Bussiere et al 2005;Cherrier et al 2003;Cherrier et al 2009;DiBlasio et al 2008;Green et al 2002;Green et al 2004;Jenkins et al 2005;Joly et al 2006;Mohile et al 2010;…”
Section: Review Characteristicsunclassified
“…None of the reviews defined cognitive impairment; however, one review calculated Reliable Change Index (RCI) data from the primary studies (Jamadar et al 2012). Many of the primary studies did not define cognitive impairment in any way.…”
Section: Definitionmentioning
confidence: 99%